Political journeys : the openDemocracy essays - Halliday, Fred (Yale University Press, 2012)
"One of the great contrarians of international relations scholarship, Fred Halliday was able to combine his understanding of the broad sweep of modern history with a profound knowledge of modern revolutions, the Middle East, and national movements. This collection of Halliday's political essays written for the online journal openDemocracy between 2004 and 2009 is proof of a subtle worldview that continues to generate questions: What is the relation between religion, nationalism, and progress? Is a new international order possible? When is intervention a force for progress? From the big headline topics such as the Iraq War to the unexpected comparisons of Tibet and Palestine, or Afghanistan and the Falklands, Halliday's writings provide a perennially surprising and enlightened guide to the major issues of international politics."--Publisher's website.